Estudo comparativo da eficiência entre trincheira de infiltração e trincheira de infiltração com uso de garrafa PET - Franchini, Tiemy (2017)
The present work has as objective to compare a conventional infiltration trench with an infiltration trench containing PET bottles, and analyze the performance of each system. Two trenches measuring 0.6 meter deep, 0.3 meter wide and 0.7 meter long were excavated, as well as their respective collection wells. The contribution areas were waterproofed, as were the sides of the trenches. The first trench was filled with sand and gravel. The second trench was filled with sand, gravel and PET bottles. Five rain simulations with different durations were carried out in both contribution areas with controlled flow of 2.7 liters / minute. Following these procedures, the retained water volumes in each trench were calculated, subtracting the present volume in the collection well from the inlet volume. The results of this study showed that the trench containing PET bottles had higher water retention, being more efficient than the conventional trench; however, the trench containing PET requires more maintenance when compared to the conventional trench.